2015
DOI: 10.1590/s0100-736x2015001000006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiothoracic ratio and vertebral heart size (VHS) to standardize the heart size of the tufted capuchin (Cebus apella Linnaeus, 1758) in computerized radiographic images

Abstract: RESUMO.-[Índice cardiotorácico e vertebral heart size (VHS) para a padronização do tamanho cardíaco do macaco-prego (Cebus apella Linnaeus, 1758) em imagens radiográficas computadorizadas.] Para a avaliação do VHS e ICT foram utilizadas radiografias toráci-cas computadorizadas de 10 macacos-prego (05 machos e 05 fêmeas) clinicamente saudáveis, oriundos do Centro de Triagem de Animais Silvestres de São Luís-MA-CETAS. Foram tomadas radiografias em projeções laterolaterais e dorsoventrais, para cálculo do Vertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…The topographical location of the heart according to the animals’ ribs, in spite of the variation among individuals, was similar to that found in primates Cebus apella where the heart silhouette was found between the third and fifth intercostal space and was close to that observed in T tetradactyla , where the base was at the height of the third rib and the apex at the height of the sixth rib. However, it was different from that found for C apella where the heart was located between the first and fifth intercostal spaces.…”
Section: Discussionsupporting
confidence: 81%
“…The topographical location of the heart according to the animals’ ribs, in spite of the variation among individuals, was similar to that found in primates Cebus apella where the heart silhouette was found between the third and fifth intercostal space and was close to that observed in T tetradactyla , where the base was at the height of the third rib and the apex at the height of the sixth rib. However, it was different from that found for C apella where the heart was located between the first and fifth intercostal spaces.…”
Section: Discussionsupporting
confidence: 81%
“…In the collared peccary, no significant statistical difference was observed between males and females for the CTR, a characteristic also observed in tonkeana and cylopis monkeys by Schillaci et al (2009), and capuchin monkeys (Cebus apella) by Rocha-Neto et al (2015) and in agoutis (Dasyprocta prymnolopha) by Moura et al (2015). These results are probably due to behavioral characteristics in captivity, both for males and females; there were no marked differences in the cardio-hemodynamic profile in this wild species, and thus there was close conformation of the cardiac silhouette between the genders.…”
Section: Discussionmentioning
confidence: 63%
“…In their study, Alves et al (12) , reported HSV values in Cebus apella to be around 9.7, while Rocha-Neto et al (8) , also recorded CTR values (0.55 +/-0.04); the animals used also showed similarities in the variations of sex and weight (12) . The values established for the species Macaca tonkeana (0.59) (7) , Macaca nigra (0.58) (7) and Macaca fascicularis (0.55 to 0.58) (7,11) validate the CTR measures identified in the present study, thus enabling the findings of cardiothoracic measurements among the species to be correlated.…”
Section: Resultsmentioning
confidence: 90%
“…it is clear that the adult females did not show great variations in the outcomes, similar to those reported in another study done with the Sapajus sp. (8) or Callithrix jacchus (9) and even in Macaca mulatta (10) ; this enabled the conclusion to be drawn that healthy adult female primates with close body shape, do not show large variations among the measurements recorded.…”
Section: Resultsmentioning
confidence: 97%